The Global Retail Sustainability: A Comparative Analysis of Environmental Management Practices and Technology Adoption Across Developed and Developing Economies - Adegoke, Omofolasaye Omobolanle; Akinyeye, Oluwaseun; Adedipe, Esther Oreoluwa; Olubiyi, Timilehin Olasoji (African Journal of Stability and Development (AJSD), 2025)
This paper focuses on the technology used to automate and support retail business functions, including environmental management across different markets. Data were obtained from Nigeria. Additionally, qualitative data from Malaysia, Sweden, and Canada provided context for the scope of the study. The study analysed ecological issues relating to international trade and consumption patterns between 2018 and 2023, highlighting how retailers responded to environmental policies in developing and developed economies. The approach adopted is a convergent parallel design, which integrates qualitative and quantitative data. In this case, primary sustainability performance data from 71 retail businesses in Nigeria were supplemented with qualitative data from other global markets. The model utilised a sustainability maturity model specifically designed for cross-cultural retail settings to assess barriers to success, performance enhancements, and change management at a particular level within a cross-cultural retail setting. The study’s outcome suggests a noteworthy difference across the regions regarding technology adoption, with the most excellent circular economy practices noted among Swedish retailers, followed by Canadian, Malaysian, and Nigerian retailers in that order. The algorithms for supply chain optimisation resulted in average waste reductions of 18-23%, while energy management systems enhanced efficiency by 14-19%. Some of the recommendations made for the study include redressing the balance of environmental performance indicators, developing self-regulatory policies on business ethics for the industry, including local communities in poverty-reduction solution design, and other mechanisms of region- and organisation-tailored implementation strategies relative to the capabilities of the organising entity.